2007
DOI: 10.1590/s0100-879x2007000400006
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between pulse oximetry and peak expiratory flow in acute asthma

Abstract: Few studies are available concerning correlations between pulse oximetry and peak expiratory flow in children and adolescents with acute asthma. Although the Global Initiative for Asthma states that measurements of lung function and oximetry are critical for the assessment of patients, it is not clear if both methods should necessarily be included in their evaluation. Since there is a significant difference in cost between pulse oximetry equipment and peak expiratory flow devices, we determined whether clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…There was significant correlation between % of expected PEFR and oxygen saturation (p value <0.0001). 8 Global initiative for asthma 2018 and British Thoracic Society 2019 guidelines recommend chest X-ray in acute exacerbations of asthma only when there is inadequate response to treatment, focal chest signs, suspicion of complications like pneumothorax, lobar collapse or consolidation, suspicion of foreign body aspiration or subcutaneous emphysema. 1,5 In this study, chest X-rays were done as indicated by these standard guidelines in 12 (24%) children on admission.…”
Section: Discussionmentioning
confidence: 99%
“…There was significant correlation between % of expected PEFR and oxygen saturation (p value <0.0001). 8 Global initiative for asthma 2018 and British Thoracic Society 2019 guidelines recommend chest X-ray in acute exacerbations of asthma only when there is inadequate response to treatment, focal chest signs, suspicion of complications like pneumothorax, lobar collapse or consolidation, suspicion of foreign body aspiration or subcutaneous emphysema. 1,5 In this study, chest X-rays were done as indicated by these standard guidelines in 12 (24%) children on admission.…”
Section: Discussionmentioning
confidence: 99%
“…Guideline recommendations include performing peak expiratory flow rate (PEFR) and pulse oximetry measurements which provide important objective assessments of asthma severity[9,10] and help to determine treatments used and need for hospitalisation[11,12]. Nebulised or inhaled beta-agonists (most commonly salbutamol) and oxygen are the main treatments advocated [6,7].…”
Section: Introductionmentioning
confidence: 99%